Developing a Marketing Strategy for Chinese restaurants on Hungry Panda in Nottingham during COVID-19 crisis - Wang, Baoyuan (2022)
COVID-19, food delivery service industry faced severe challenges in the UK (Panzone et al., 2021).Chinese restaurant, as small and family-run restaurants, were facing more severe challenges than chain restaurants in UK (Chaudhry and Crick, 2004; Najib et al., 2021). Several studies have emphasized the importance of O2O food delivery platform due to the change in food consumption behavior (Yang et al., 2021; Tan et al., 2021). However, previous research has not explored Chinese restaurants on Hungry Panda in Nottingham. The aim of this research is to explore current marketing situation of Chinese restaurants on Hungry Panda in Nottingham, so as to develop marketing strategies for these restaurants. This research applied a mixed-method approach, including 145 surveys among the Chinese consumers who order takeaways from Chinese restaurants on Hungry Panda in Nottingham during COVID-19, and 8 semi-structured interviews with managers of Chinese restaurants on Hungry Panda in Nottingham. Based on quantitative data, Chinese consumers are mainly 18–25 year olds and students. Through correlation analysis, this research found that food quality, food hygiene, food price, e-service quality, home delivery service quality, and home delivery service hygiene have significant impacts on Chinese consumers’ satisfaction with Chinese restaurants on Hungry Panda. Through thematic analysis, this research found that the restaurants interviewed still face challenges, including decrease in sales, financial pressure, difficulties in business model transformation, and raw material supply difficulties. Meanwhile, restaurants still need to further adjust their strategies in response to COVID-19. The findings of this research highlight the importance of improving marketing strategy for restaurants on O2O food delivery platforms. Moreover, it is important for managers of restaurants to consider consumers’ characteristics, consumers’ satisfaction, and challenges faced by their restaurants while using STP strategy and 4P’s marketing strategy.